Dilated ascending aorta in the fetus. (8th July 2021) - Dumitrascu‐Biris, Ioana; Zidere, Vita; Vigneswaran, Trisha; Charakida, Marietta; Mathur, Sujeev; Kametas, Nick; Simpson, John
Abstract: Introduction: Prenatal recognition of dilated aortic root is extremely rare and there are significant challenges in counselling these patients. The primary aim of this case series is to describe the prevalence, associations and outcome of dilated ascending aorta diagnosed during fetal life. Methods: This is a retrospective cohort study from two tertiary fetal cardiology centres. Dilated ascending aorta was defined as gestation‐specific standard deviation > 1.96 at some point during gestation. Results: Sixteen infants were live born and underwent postnatal echocardiography. Prenatally suspected bicuspid aortic valve (BAV) ( n  = 6) was confirmed in 5 cases (83%) postnatally. Thirteen children have been followed up for a period of minimum one year. No connective tissue disease was found. Conclusions: Prenatal dilated ascending aorta is a rare finding (0.06%). It is associated with BAV in 37% of cases and extracardiac abnormalities in 15.7%. Nuchal translucency measurement was >3.5 in 13% of cases. Connective tissue disease was not diagnosed postnatally. This is the largest prenatal cohort with dilated ascending aorta and postnatal outcomes to date. We showed a postnatal persistence of ascending aortic dilatation in 43% of babies. In the absence of extra‐cardiac abnormalities, medium term outcome appears good but postnatal surveillance of aortic dilation is required. Key Points: What is already known about this topic? Dilation of the ascending aorta in patients with bicuspid aortic valve (BAV) may be present from infancy. What does this study add? Dilatation of the ascending aorta can be recognized during fetal life. The most common association of dilated ascending aorta in fetal life is of a bicuspid aortic valve. In the absence of extra‐cardiac abnormalities, medium term outcome appears good but postnatal surveillance of aortic dilation is required.